(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2021)
In every country, regional social concepts are of significance in the political environment. In Indonesia, about 40% of the population are ethnic Javanese. Accordingly, their cultural concepts bear a considerable influence on the political map and presidential elections. As a large community, the Javanese hold on to longstanding historical notions of the position of the ruler and the wong cilik or commoner in the mechanics of governance and governmental administration. In Javanese social stratification, the ruler and the people are conceptualised and positioned in different ways compared with governance in modern democratic societies. Two broad social levels can be distinguished the wong cilik, consisting of peasants and the city lower classes, and the priyayi (or ruling elite and high class society). They can be somehow compared with the traditional classification of the proletariat or the working class and the bourgeois, the holders of the means of production. Both have their own social and economic life but have an interdependent relationship of exchanging services and goods. This relationship is known in Java as kawula and gusti, a cultural “patron-client” relation, containing supporting reciprocally based on authority.